2019
DOI: 10.1103/physrevapplied.12.064049
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Capacitive Coupling Within a Quadruple-Quantum-Dot Array

Abstract: We present measurements of the capacitive coupling energy and the inter-dot capacitances in a linear quadruple quantum dot array in undoped Si/SiGe. With the device tuned to a regime of strong (>1 GHz) intra-double dot tunnel coupling, as is typical for double dot qubits, we measure a capacitive coupling energy of 20.9 ± 0.3 GHz. In this regime, we demonstrate a fitting procedure to extract all the parameters in the 4D Hamiltonian for two capacitively coupled charge qubits from a 2D slice through the quadruple… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 46 publications
4
27
0
Order By: Relevance
“…We have investigated the realization of single-step twoqubit gates in capacitively coupled flopping-mode spin qubits. In particular, by calculating the Makhlin invariants from the physical Hamiltonian for the qubit-qubit interaction, we have demonstrated that multiple two-qubit quantum gates can be realized with the same setup by using realistic experimental parameters [31,47,48]. Interestingly, a variety of two-qubit gates can be realized with fidelity higher than 95%, even accounting for dephasing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have investigated the realization of single-step twoqubit gates in capacitively coupled flopping-mode spin qubits. In particular, by calculating the Makhlin invariants from the physical Hamiltonian for the qubit-qubit interaction, we have demonstrated that multiple two-qubit quantum gates can be realized with the same setup by using realistic experimental parameters [31,47,48]. Interestingly, a variety of two-qubit gates can be realized with fidelity higher than 95%, even accounting for dephasing.…”
Section: Discussionmentioning
confidence: 99%
“…[11,44]; in experiments, they are directly accessible but depend on the geometry and gates and are necessarily renormalized due to unavoidable screening effects [31]. Hence, below we consider values of the inter-DQD coupling |g| ∼ 15 − 30 μeV as reported in recent experiments [31]. Notice that we assume that any exchange coupling is strongly suppressed due to the absence of tunneling between the two DQDs.…”
Section: Model and Low-energy Hamiltonianmentioning
confidence: 99%
See 1 more Smart Citation
“…To perform capacitively-coupled two-qubit measurements, we fabricate a linear chain of four quantum dots using an overlapping-aluminum gate architecture (Fig. 1a) 14,15,20,21 . The fabrication details for this device have been reported elsewhere 15 .…”
Section: Device Detailsmentioning
confidence: 99%
“…1a) 14,15,20,21 . The fabrication details for this device have been reported elsewhere 15 . Measurements are performed in an Oxford Triton 400 dilution refrigerator with a~15 mK mixing chamber temperature.…”
Section: Device Detailsmentioning
confidence: 99%